Pyridine-pyrazole based Al(iii) 'turn on' sensor for MCF7 cancer cell imaging and detection of picric acid. Issue 17 (9th March 2021) - Saha, Sayan; De, Avik; Ghosh, Arijit; Ghosh, Avik; Bera, Kaushik; Das, Krishna Sundar; Akhtar, Sohel; Maiti, Nakul C.; Das, Abhijit Kumar; Das, Benu Brata; Mondal, Raju
Abstract : We report herein the development of a new pyridine-pyrazole based bis-bidentate asymmetric chemosensor that shows excellent turn-on chelation-enhanced Al 3+ -responsive fluorescence. Abstract : We report herein the development of a new pyridine-pyrazole based bis-bidentate asymmetric chemosensor that shows excellent turn-on chelation-enhanced Al 3+ -responsive fluorescence. The presence of two 'hard' phenolic hydroxyl groups plays a pivotal role in switching-on the sensing through coordination to the 'hard' Al 3+ ion, while the mechanism can be interpreted by the chelation-enhanced fluorescence (CHEF) process. The X-ray single structure show a planar conjugated structure of the ligand, which was further stabilized by extensive H-bonding and π–π stacking. The photophysical studies related to the sensing behavior of the titular ligand toward aluminum was investigated in detail using various spectroscopic techniques like UV-Vis, photoluminescence, fluorescence and time-correlated single-photon count (TCSPC) and time-resolved NMR. The spectroscopic methods also confirm the selective detection of Al 3+ ion in the presence of other metal ions. The theoretical calculations using Density Functional Theory (DFT) and the Time Dependent Density Functional Theory (TD-DFT) provide further insight on the mechanistic aspects of the turn-on sensing behavior including the electronic spectra of both the ligand and the complex. Interestingly, the as-synthesized H2 DPC–Al complex can also be utilized as a fluorescence-based sensor for various nitroaromatics including picric acid, for which an INHIBIT logic gate can also be constructed. The as synthesized complex was subsequently used as a fluorescent probe for imaging of human breast adenocarcinoma (MCF7) cells using live cell confocal microscopic techniques.